PERSEPSI TERHADAP GAME EDUKASI QUIZIZZ PADA MATA PELAJARAN MATEMATIKA SMP SWASTA KAPUAS PONTIANAK - Titin Titin (LPD IKIP PGRI Pontianak, 2023)
Abstract: Education is essentially preparing efforts so that humand develop with various kinds of useful knowledge to participate in the development of the world of education and make a real contribution to nation building. In the learning process inside the classroom and outside it creates perceptions for each student, the perceptions that arise from each student are of course different, student perception is a process og giving meaning to the surrounding environment. This study aims to determine and describe studentâ€™s perceptions of the typy of case study research. The subjects in the 2022/2023 academic year, totaling 9 respondents.Data collection techniques used in this study were quetionnaires, interviews and documentation. The results of this study indicate that the perceptions of grade 8 students at Kapuas Pontianak Private Middle School. The application can help students to remember the material presented by the teacher and students.Keywords:GAME EDUKASIÂ QUIZIZZÂ